Non-extraction treatment of severe crowding with pendulum appliance - Chandrasekhar Gandikota; Yudhister Palla Venkata; Padmalatha Challa; Shubhaker Rao Juvvadi (Wolters Kluwer Medknow Publications, 2013)
An extraction case was planned for non-extraction treatment using pendulum appliance and the effect of appliance was evaluated in a 14-year-old girl with a severe maxillary and mandibular crowding followed by non-extraction fixed appliance preadjusted edgewise appliance mechanotherapy. Total treatment time was for 22 months. The obtuse nasolabial angle was maintained intact. Correction of crowding, co-ordinated arch forms was achieved with molar distalization. The impetus on soft-tissue paradigm is stressed in this case report and pendulum appliance can indeed boost our clinical acumen and swing our priorities toward non-extraction treatment.